Understanding helium transport: experimental and theoretical investigations of low-Z impurity transport at ASDEX Upgrade. (27th March 2019) - Kappatou, A.; McDermott, R.M.; Angioni, C.; Manas, P.; Pütterich, T.; Dux, R.; Viezzer, E.; Jaspers, R.J.E.; Fischer, R.; Dunne, M.G.; Cavedon, M.; Willensdorfer, M.; et al.
Abstract: The presence of helium is fundamentally connected to the performance of a fusion reactor, as fusion-produced helium is expected to heat the plasma bulk, while He 'ash' accumulation dilutes the fusion fuel. An understanding of helium transport via experimentally validated theoretical models of the low-Z impurity turbulent transport is indispensable to predict the helium density profile in future fusion devices. At ASDEX Upgrade, detailed, multi-species investigations of low-Z impurity transport have been undertaken in dedicated experiments, resulting in an extensive database of helium and boron density profiles over a wide range of parameters relevant for turbulent transport (normalised gradients of the electron density, the ion temperature, and the toroidal rotation profiles, the collisionality and the electron to ion temperature ratio). Helium is not found to accumulate in the parameter space investigated, as the shape of the helium density profile follows largely that of the electron density. Helium is observed to be as peaked as the electron density at high electron cyclotron resonance heating fraction, and less peaked than the electron density at high neutral beam heating fraction. The boron density profile is found to be consistently less peaked than the electron density profile. Detailed comparisons of the experimental density gradients of both impurities with quasilinear gyrokinetic simulations have shown that a qualitative agreement between experiment and theory cannot always be obtained, with strong discrepancies observed in some cases.